VEHICLE IDENTIFICATION MARKINGS ON MERCEDES BENZ PASSENGER CARS AND TRUCKS - E. Chesnokova; S. Kulik; A. Kondakov (Теория и практика судебной экспертизы)
The paper explores the markings applied by Mercedes Benz in the manufacture of passenger cars and trucks. An algorithm is offered for the verification of vehicle identification markings. Special software has been developed on the basis of this algorithm and contains a virtual factual database.